(untitled) (Journal of the College of Basic Education, 2022)
The Lebanese arena witnessed many parties and personalities, which influenced and were affected by the Lebanese society, and the most prominent of these personalities was Anton Saadeh, a politician, journalist, linguist and philosopher. After the founding of the Syrian Social Nationalist Party, writing about Antoun Saadeh is of great importance, as this is a topic and because of the discussion and controversy it sparked around him between those who agreed with his views and those who rejected them.